Profile of Radiation Therapy after Radical Prostatectomy: Experience in a Tertiary Hospital in Jakarta, Indonesia - Rama Firmanto; Agus Rizal AH Hamid; Chaidir Arif Mochtar; Rainy Umbas (National Cancer Center - Dharmais Cancer Hospital, 2020)
Background: Despite the high recurrence rate, radical prostatectomy (RP) remains as a preferable surgical treatment of localized prostate cancer. Adjuvant radiotherapy (ART) and salvage radiotherapy (SRT) are available approaches in preventing biochemical progression after RP. We aim to investigate the use of radiotherapy, both ART and SRT, in those who underwent RP.Methods: We used a retrospective cohort study design, with samples recruited from prostate cancer patients who underwent RP between January 2008 and December 2016. Patients who had undergone RP at Cipto Mangunkusumo Hospital, Jakarta, Indonesia were included in the present study. More in detail, three and five subjects were treated with ART and SRT, respectively. We only included those who had a minimum of one year of follow-up. Variables including age, preoperative prostate-specific antigen (PSA), clinical staging, pathological staging, Gleason score, and death were recorded. We analyzed the overall survival time using the Kaplan-Meier method.Results: From 34 patients included in the study, 26 underwent RP alone, while 5 patients underwent adjuvant radiotherapy and 3 patients underwent salvage radiotherapy after RP. The mean ages in the three groups were 61.46 ± 5.76, 58.2 ± 4.86 and 62.67 ± 7.5, respectively. The preoperative PSA value was above 10 mg/dL in 61.5% in patients without RT, 100% in patients with ART after RP, and none in SRT. 17 (51.5%) out of 33 subjects were ≥T2 clinical stage and 24/30 (80%) subjects were ≥pT2. Timing for ART and SRT ranged from 1.07 to 6.3 and 5.27 to 21.43 months after RP, respectively. The 10-year survival rates were 84.6% in patients with RP alone, 80% in patients with ART+RP, and 66.7% in patients with SRT+RP. The average survivals of those who had RP alone as well as ART and SRT were 44.56 ± 32.64, 46.79 ± 24.02, and 71.71 ± 38.74 months.Conclusions: The average survival of those who received SRT is better than those who underwent ART and RP alone. Prospective studies with larger samples are needed to evaluate the efficacy of radiation therapy after radical prostatectomy.